THE IMPACT OF HOME ENVIRONMENT AND SOCIO-ECONOMIC FACTORS ON ENGLISH LANGUAGE ACQUISITION (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2026)
This research explores the critical role of the domestic environment in the process of English language acquisition. Drawing upon the theoretical frameworks of Berstein (1970) and Bradley and Caldwell (1984), the study examines how home-based variables—ranging from socio-economic status to parental involvement—influence academic outcomes. The literature review highlights a three-stage evolution in environmental research, shifting from global social factors to specific interactions between the child and their surroundings. Furthermore, the study incorporates Liando’s (2007) findings regarding the "support gap" in EFL contexts and emphasizes the detrimental effects of family stress, as noted by Alwin and Thornton (1984). The results suggest that while financial resources (Bourdieu, 1990) provide necessary tools, it is the psychological stability and active parental guidance that directly foster linguistic fluency.
Keywords: Home environment, EFL acquisition, parental involvement, socio-economic status, academic achievement.